2001
DOI: 10.1111/j.1651-2227.2001.tb01605.x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary excretion of free cysteine in critically ill neonates

Abstract: In preliminary observations, significant amounts of free cysteine, a neurotoxic amino acid, were noted in the urine of asphyxiated or septic‐shocked neonates. The present study was conducted to determine whether free urinary cysteine was elevated in these critically ill neonates compared with a control group, and to assess the clinical significance of this generation. Free cysteine was measured in the urine of newborn infants with perinatal asphyxia (n= 16) or neonatal sepsis (n= 14) and the urine of a control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The safe upper level for sulfite plasma concentration is not known, but many adverse effects have been reported after exposure to exogenous sulfites (Smolinske 1992), including the development of seizures following administration of morphine containing sodium bisulfite (Meisel and Welford 1992). Cambonie et al (2001) described elevated urinary cysteine excretion in neonates with septic shock compared with well neonates and showed that cysteine excretion was indirectly related (the proposed mechanism being nonenzymatic sulphitolysis) to the amount of sulfite administered by drug infusions. Some of these children also had positive urine sulfite test strips and mildly elevated sulfocysteine excretion.…”
Section: Csf Plp In Disorders Of Sulfite Accumulationmentioning
confidence: 97%
“…The safe upper level for sulfite plasma concentration is not known, but many adverse effects have been reported after exposure to exogenous sulfites (Smolinske 1992), including the development of seizures following administration of morphine containing sodium bisulfite (Meisel and Welford 1992). Cambonie et al (2001) described elevated urinary cysteine excretion in neonates with septic shock compared with well neonates and showed that cysteine excretion was indirectly related (the proposed mechanism being nonenzymatic sulphitolysis) to the amount of sulfite administered by drug infusions. Some of these children also had positive urine sulfite test strips and mildly elevated sulfocysteine excretion.…”
Section: Csf Plp In Disorders Of Sulfite Accumulationmentioning
confidence: 97%
“…Cysteine is a crucial limiting factor in glutathione synthesis 62 and excessive urinary excretion of cysteine is observed in critically ill neonates. 63 The amino acid cysteine is found in whey protein, which constitutes 60 per cent of human breast milk. 64 …”
Section: Condition Assessedmentioning
confidence: 99%